KEPENTINGAN OMAN SEBAGAI TUAN RUMAH ASIAN BEACH GAMES II MUSCAT TAHUN 2010 - Ardianyah "; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the interest of Oman to create a Asian Beach Games II in Muscat 2010. Conflict politics, social and security in Middle East has been influence to region generally and to Oman. This conflict influence the bad image of Oman in international world.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze interest of Oman to create a Asian Beach Games II in Muscat 2010. The theories applied in this research are realisme perspective, national interest concept from Donald. E. Nuchterlain.The research shows that interest of Oman to create a Asian Beach Games II in Muscat 2010 to move the bad image of Oman to international world. To erased this image Oman create a Asian Beach Games II in Muscat 2010Key words: interest, image, diplomacy and Asian Beach Games